The effects of urbanization on aquatic ecosystems in peri-urban protected areas of Mexico City: The contradictory discourse of conservation amid expansion of informal settlements. (March 2021) - Caro-Borrero, Angela; Carmona-Jiménez, Javier; Rivera-Ramírez, Karla; Bieber, Kaitlen
Highlights: Socio-environmental analysis of conservation dynamics in a peri-urban micro-basin. Conservation challenge in megacities, social priorities and environmental blindness. Environmental and social consequences of the expansion of informal human settlements. Abstract: Years of population growth and urban expansion have affected ecologically forested areas outlying Mexico City. To control the growth and the negative impact on natural areas, the Conservation Land act of 1987s declared protection of non-populated forest areas. However, this initiative has been overshadowed by the growing demand of affordable housing. The expansion of housing in protected areas has been coupled with unclear guidelines from local authorities in restricting domestic growth. This study focuses on the Magdalena River micro-basin, which is key to freshwater provisioning to Mexico City. The objective of this research is to show the socio-ecological effects of urbanization and the lack/misguidance of local governance on the Magdalena River. Ecological quality was assessed through identifying hydro-morphological quality and bioindicators such as macroinvertebrates and macroalgae. This information was paired with social data collected through an archival study of historical literature, and interviews with residents who are both lawfully and unlawfully living within protected areas. The results show that the ecological quality of the Magdalena River is undergoing significant changes because of an influx of nutrients and external alterations made to the riparian zone. Pollution from housing, restaurants, and trout farms are the factors most directly related to the changes. Additionally, we encountered little to no federal/local policy aimed at controlling inputs and altercations to the river. Our study has shown that urbanization within the micro-basin negatively alters the biological diversity. The growth further facilities the increase of fecal bacteria posing a risk to human health. Social data from interviews and the literature review showed the ecological importance of the area to the local people. In the past there have been two cases of restoration efforts made by the municipal government, but their intentions for restoration ultimately failed. In both efforts were poorly planned and were not communicated with local people nor did they include local participation. As a consequence, the locals have a general distrust of the external stakeholder. Apart from local development misinformation and unwelcome restoration intervention, there is a long history of governmental authorities incurring acts of corruption and bribery. Many unauthorized settlements are unaware or have not been educated about the environmental impact they are having on ecosystems and are often overlooked or excluded when it comes to creating policy. In conclusion, local participation and approval is essential to the creation of a successful management plan, thus it is important governmental officials seek their involvement. Conservation land within the micro-basin is insufficient to protect the ecological integrity of ecosystems as both landowners and local authorities are facilitating unsustainable practices that transit between the vision on paper of a sustainable city and the lack of concrete facts to achieve it.